A survey on the sustainable library practices and trends of selected academic libraries in Metro Manila - Silverio, Rochelle S. (School of Library and Information Studies, University of the Philippines Diliman, 2011)
The library as an organization and as an integral part of society has a responsibility in protecting the environment. This study would like to make an inquiry on how academic libraries play their role in the environmental movement by looking into the different aspects of library sustainability. Forty-three libraries of the 55 member institutions of the Philippine Association of Tertiary Level Educational Institutions in Environmental Protection and Management in the National Capital Region participated in the study. Two research instruments were utilized to gather data: (1)the survey questionnaire which asks about the library's basic information, environmental sustainability policies and programs, sustainable library practices, and the librarian's perception on the environment; and (2)the Lightning Efficiency Index Computation.